The Photodynamic Properties and the Genotoxicity of Heat-Treated Silicalite-1 Films - Jirka, Ivan; Kopová, Ivana; Kubát, Pavel; Tabor, Edyta; Bačáková, Lucie; Bouša, Milan; Sajdl, Petr (Materials (Basel, Switzerland), 2019)
We investigated the use of a supported silicalite-1 film (SF) as a promising coating for metallic materials used in the fabrication of prostheses. The role of carbonaceous residua present on high-temperature calcined-SF in generating singlet oxygen for future use as a sterilization method has also been addressed, and the potential genotoxicity of these residua in osteoblast-like cells has been investigated. Calcination of as-synthesized SF induced the appearance of a rather complicated mixture of aliphatic and aromatic species on its outer surface. A series of variously volatile polycyclic aromatic hydrocarbons (PAH), including naphthalene, fluorene, phenanthrene, anthracene, fluoranthene, and pyrene, were identified in micromole concentrations. Irradiation of these PAHs on calcined-SF immersed in air-saturated chloroform led to the formation of very low concentrations of singlet oxygen. However, an increased level of DNA damage was observed on calcined-SF by immunofluorescence staining of phosphorylated histone H2AX analyzed by flow cytometry.
Keywords: singlet oxygen; surface coating; genotoxicity; implant material